Drone and Electrical Resistivity Tomography (ERT) survey assisted slope instability risk assessment: A case study of Phyllitic landslide in Lesser Himalayas of Nepal (LTU Journal of Advanced Computing & Engineering, 2026)
This study investigates the geological and geotechnical drivers of roadside slope failures along the Khanigaon Rural Municipality-2 (Likhu) road section in Nuwakot, Nepal, where excavation for road expansion has triggered landslides with significant socio-economic consequences. Geologically situated within the Seti Formation, the area consists of grey-greenish gritty phyllites and conglomerates, which were analyzed through a combination of Electrical Resistivity Tomography (ERT) and laboratory testing. The investigation identified a critical slip surface between 1 m and 6 m depth within Sandy Silt (ML) and Sandy Lean Clay (CL) soils characterized by low cohesion (1-11 kN/m2) and friction angles (26.5-30°). Stability modeling using the Limit Equilibrium Method (LEM) via Geo-studio and Slide2 software yielded an initial Factor of Safety (FoS) (Geo-studio FoS=0.668, and Slide2 FoS=0.679) as low as 0.668, confirming a high risk of soil slope failure despite rock stability. While the removal of loose materials was found insufficient to stabilize the site (Geo-studio FoS=0.828, and Slide2 FoS=0.832), a proposed integrated design comprising a reinforced concrete shear wall, concrete cribs, and 25 mm diameter anchor bolts successfully increased the FoS to 1.84. This research concludes that combining these structural reinforcements with bio-engineering vegetation offers a sustainable and technically sound solution for Himalayan infrastructure restoration.